The Antimicrobial Activity of the AGXX® Surface Coating Requires a Small Particle Size to Efficiently Kill Staphylococcus aureus - Linzner, Nico; Antelmann, Haike (Frontiers in Microbiology, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) isolates are often resistant to multiple antibiotics and pose a major health burden due to limited treatment options. The novel AGXX® surface coating exerts strong antimicrobial activity and successfully kills multi-resistant pathogens, including MRSA. The mode of action of AGXX® particles involves the generation of reactive oxygen species (ROS), which induce an oxidative and metal stress response, increased protein thiol-oxidations, protein aggregations and an oxidized bacillithiol redox state in S. aureus. In this work, we report that the AGXX® particle size determines the effective dose and time-course of S. aureus USA300JE2 killing. We found that the two charges AGXX®373 and AGXX®383 differ strongly in their effective concentrations and times required for microbial killing. While 20-40 µg/ml AGXX®373 of the smaller particle size of 1.5-2.5 µm resulted in >99.9 % killing after 2 hours, much higher amounts of 60-80 µg/ml AGXX®383 of the larger particle size of >3.2 µm led to a >99 % killing of S. aureus USA300JE2 within 3 hours. Smaller AGXX® particles have a higher surface/volume ratio and therefore higher antimicrobial activity to kill at lower concentrations in a shorter time period compared to the larger particles. Thus, in future preparations of AGXX® particles, the size of the particles should be kept at a minimum for maximal antimicrobial activity.